Clinical and molecular characterization of Rubinstein‐Taybi syndrome patients carrying distinct novel mutations of the EP300 gene. (17th February 2014) - Negri, G.; Milani, D.; Colapietro, P.; Forzano, F.; Della Monica, M.; Rusconi, D.; Consonni, L.; Caffi, L. G.; Finelli, P.; Scarano, G.; Magnani, C.; Selicorni, A.; et al.
<x xml:space="preserve">Abstract</x> Rubinstein‐Taybi syndrome (RSTS) is a rare congenital neurodevelopmental disorder characterized by postnatal growth deficiency, skeletal abnormalities, dysmorphic features and cognitive deficit. Mutations in two genes, CREBBP and EP300, encoding two homologous transcriptional co‐activators, have been identified in ˜55% and ˜3–5% of affected individuals, respectively. To date, only eight EP300‐mutated RSTS patients have been described and 12 additional mutations are reported in the database LOVD. In this study, EP300 analysis was performed on 33 CREBBP‐negative RSTS patients leading to the identification of six unreported germline EP300 alterations comprising one deletion and five point mutations. All six patients showed a convincing, albeit mild, RSTS phenotype with minor skeletal anomalies, slight cognitive impairment and few major malformations. Beyond the expansion of the RSTS‐EP300‐mutated cohort, this study indicates that EP300‐related RSTS cases occur more frequently than previously thought (˜8% vs 3–5%); furthermore, the characterization of novel EP300 mutations in RSTS patients will enhance the clinical practice and genotype–phenotype correlations.